2008
DOI: 10.1038/sj.bjc.6604376
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of ketoconazole on exposure to temsirolimus following intravenous infusion of temsirolimus

Abstract: Intravenous (i.v.) temsirolimus, a novel inhibitor of mammalian target of rapamycin, is approved for the treatment of advanced renal cell carcinoma and is being studied in patients with mantle cell lymphoma. Because temsirolimus and its primary metabolite, sirolimus, are metabolised by the cytochrome P450 3A4 pathway (CYP3A4), the potential exists for pharmacokinetic (PK) drug interactions with the numerous agents that modulate CYP3A4 isozyme activity. We investigated the effects of ketoconazole, a potent CYP3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…P450-inducing anticonvulsant agents resulted in 73% and 50% lower C max and AUC values, respectively [45]. If a concomitant strong CYP3A4 inhibitor is necessary, a temsirolimus dose reduction to 12.5 mg weekly should be considered [46]. In vitro studies showed that temsirolimus and sirolimus inhibit the CYP2D6 isozyme (K i ϭ 1.5 and 5 M, respectively), indicating a potential for PK interaction with agents that are substrates of CYP2D6.…”
Section: Drug and Complementary And Alternative Medicine Interactionsmentioning
confidence: 99%
“…P450-inducing anticonvulsant agents resulted in 73% and 50% lower C max and AUC values, respectively [45]. If a concomitant strong CYP3A4 inhibitor is necessary, a temsirolimus dose reduction to 12.5 mg weekly should be considered [46]. In vitro studies showed that temsirolimus and sirolimus inhibit the CYP2D6 isozyme (K i ϭ 1.5 and 5 M, respectively), indicating a potential for PK interaction with agents that are substrates of CYP2D6.…”
Section: Drug and Complementary And Alternative Medicine Interactionsmentioning
confidence: 99%
“…First, potential effects of higher exposures on the QTc interval were not addressed and cannot be ruled out. Temsirolimus is a substrate of CYP3A4, and concomitant administration of a CYP3A4 inhibitor, such as ketoconazole, has no effect on temsirolimus C max or AUC; however, a strong PK interaction leading to increased exposure of the primary metabolite sirolimus (C max , 2.2-fold; AUC, 3.1-fold) was observed [17]. In our study, PK/PD modeling indicated no relationship between temsirolimus or sirolimus exposure and prolongation of the QTc interval, but vigilance is still warranted and a temsirolimus dose reduction to 12.5 mg should be considered if administered with CYP3A4 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The application of P450-inducing anticonvulsant agents resulted in lower C max and AUC values [46]. If a concomitant strong CYP 3A4 inhibitor is necessary, a temsirolimus dose reduction to 12.5 mg weekly should be considered [48]. Other studies demonstrated that temsirolimus inhibits the CYP 2D6 isoenzyme, indicating a potential for interactions with agents that are substrates of CYP 2D6 [49].…”
Section: Drug and Food Interactionmentioning
confidence: 93%